Answer:
Simplifying
16y + 14 + -14y + -12 = 0
Reorder the terms:
14 + -12 + 16y + -14y = 0
Combine like terms: 14 + -12 = 2
2 + 16y + -14y = 0
Combine like terms: 16y + -14y = 2y
2 + 2y = 0
Solving
2 + 2y = 0
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-2' to each side of the equation.
2 + -2 + 2y = 0 + -2
Combine like terms: 2 + -2 = 0
0 + 2y = 0 + -2
2y = 0 + -2
Combine like terms: 0 + -2 = -2
2y = -2
Divide each side by '2'.
y = -1
Simplifying
y = -1